BACKGROUND, TEACHING AND MEMOIRS OF A FEMALE EDUCATOR: FRAGMENTS OF RURAL TEACHING IN NOVO HAMBURGO/RS 1940-1969 - De Souza, José Edimar (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This investigation aims into life facts and conclusions on education from the view of a basic school female educator  whose career was developed in countryside of Novo Hamburgo/ RS between 1940 and 1969. This article is directly related to a further investigation about career development and performance of people that were educated as teachers but didn’t get to work in different level classrooms in public schools at Novo Hamburgo in the  rural side during 1940 y 2009.This special work comes from analyzing teaching at different areas of the country part in Lomba Grande, areas that were part of a female educator named Gersy during her teaching methods development, we establish her story from different level classrooms. This investigation is mainly analytical by use of aural history, and some semi-structured interviews. Theorical framework is mainly based in cultural History perspectives and memoirs as a study document. Subject of study is an educator that even though her youth and lack of experience in parenting and teaching was able to realize of her choice on teaching and her pedagogical practice that made an evidence that experience made part of knowledge building  and teaching. This educator’s memoirs allowed a new approach and to know about begining of public shools in Lomba Grande, emphassising  into the background  process of isolated schools, as a feature that identifyed her as an Educator.